Hernia trauma (blunt inguinal hernia trauma): About a case - Segura, Daisy; Estrugo, Roberto (Cirugía del Uruguay, 1997)
The authors present an infrequent case of abdominal trauma in a carrier of inguinal hernia. They discuss special features as regards physiopathology, diagnosis and therapeutics of these patients. They advise integral therapeutics of lesions, including parietal repair in the presence of locorregional bacteria/ contamination.